INOVASI PENDIDIKAN SEBAGAI UPAYA MENYELESAIKAN MASALAH DALAM PENDIDIKAN - Marroan Rajoki Hasibuan; Abdul Muttaqin Rusydi; Lulu Syabrina; Dinda Dyah Pitaloka (Kampus Akademik Publiser, 2024)
The aim of writing this article is to examine educational innovation as an effort to solve problems in education. The purpose of this writing is to find out the meaning of educational innovation and educational innovation efforts in solving problems in education. This article emphasizes the importance of innovation in education as a step to overcome various educational problems in Indonesia. Education and society have a reciprocal relationship, meaning that the conditions of the world of education reflect the complex realities of society. However, this reciprocal relationship is not always consistent. Society is developing rapidly and progressively, while the world of education is still grappling with various problems that are difficult to overcome. Therefore, innovation in the field of education is very important and urgent for parties who care about educational development, as an effort to advance education in Indonesia. The writing methodology in this article is to use literature review. Literature review is the first and important step in preparing a research plan. Literature study is a search and research of the literature by reading various books, journals, mass media and other publications related to the research topic, to produce an article regarding a particular topic or issue. This method is also supported by the descriptive method, namely research that attempts to describe phenomena, events and occurrences that occur in the present. By formulating the problem until finally making a conclusion.